TALKING POINTS FOR MEETING ABOUT GRAY ROBERTSONS MEDIA TOUR] - MARCUS R (Tufts Archival Research Center, 2007)
Letter from Richard Marcus to Susan Stuntz regarding the media tour of Grey Robertson. Indicates that one of the goals of the tour is to garner support around sick builiding syndrome and state and local labor unions. Contains a list of key contacts in certain cities that could be of aid in achieving these goals.